The Relationship among Fossil Fuel Energy, Economic Development, Institutional Quality, Globalization, Foreign Direct Investment and Forest in European Countries - Pardaev, Jamshid; Ibadullaev, Dilshad; Kurbanov, Ziyat; Eshov, Mansur; Artiqova, O’g’iljon; Mutaliyeva, Lyailya (International Journal of Energy Economics and Policy, 2025)
Currently, the harmful nature of fossil fuel is being discussed in the forest context in Europe. Therefore, this research examines the effect of fossil fuel energy on forest area in the panel of 39 European countries during the period 2000-2024. For the empirical estimations, Quantile regression estimated through the Method of Moments framework is employed which is robust to heteroscedasticity. The findings reveal that fossil fuel energy negatively and significantly impacts on forest area across all the quantiles from 10% to 90%. Policy implications should prioritize the role of fossil energy in shaping forest policy.